Implementation of the PsoWell™ Model for the Management of People with Complex Psoriasis - Hewitt, R; Pattinson, R; Cordingley, L; Griffiths, C; Kleyn, E; McAteer, H; Schofield, J; Bundy, C (Acta dermato-venereologica, 2021)
The Psoriasis and Well-being (PsoWell)™ training programme, incorporating motivational interviewing, improves clinicians' knowledge and skills to manage complex psoriasis, including behaviour change. The aims of this study were to deliver the PsoWell™ training programme to dermatology specialists, and to evaluate the acceptability and feasibility of implementing the PsoWell™ model across dermatology services. Framework analysis of 19 qualitative semi-structured interviews was performed, following delivery of nine, 1-day PsoWell™ training days involving 119 participants. Two themes were identified: "Perceptions and Priorities" and "Awareness", sub-divided into: "Awareness Not Competence" and "Increasing Awareness". The PsoWell™ model was found to be acceptable and feasible to implement across dermatology settings. Participants were more skilled and motivated to address psycho-logical issues, including behaviour change, but wanted further training to ensure competency. The trainees claimed that scepticism among some colleagues regarding whole-patient management might prevent uptake. Data show-ing the impact on health outcomes are needed and might overcome scepticism. Remote consultation could adopt the PsoWell™ approach.